Dual Functionality of HIV-1 Vif in APOBEC3 Counteraction and Cell Cycle Arrest - Salamango, Daniel J.; Harris, Reuben S. (Frontiers in Microbiology, 2021)
Accessory proteins are a key feature that distinguishes primate immunodeficiency viruses such as HIV-1 from other retroviruses. A prime example is the virion infectivity factor, Vif, which hijacks a cellular co-transcription factor (CBF-b) to recruit a ubiquitin ligase complex (CRL5) to bind and degrade antiviral APOBEC3 enzymes including APOBEC3D (A3D), APOBEC3F(A3F), APOBEC3G (A3G), and APOBEC3H (A3H). Although APOBEC3 antagonism is essential for viral pathogenesis, and a more than sufficient functional justification for Vif’s evolution, most viral proteins have evolved multiple functions. Indeed, Vif has long been known to trigger cell cycle arrest and recent studies have shed light on the underlying molecular mechanism. Vif accomplishes this function using the same CBF-b/CRL5 ubiquitin ligase complex to degrade a family of PPP2R5 phospho-regulatory proteins. These advances have helped usher in a new era of accessory protein research and fresh opportunities for drug development.